KAJIAN PEMELIHARAAN KENDARAAN DAN PERALATAN GROUND SUPPORT EQUIPMENT UNTUK MENDUKUNG KESELAMATAN PENERBANGAN DI SISI UDARA BANDAR UDARA SULTAN THAHA JAMBI - Dian Dwi Indriyani; Nawang Kalbuana; Irwan Faizal (FTK UNSURYA, 2026)
This study reviews the feasibility of Ground Support Equipment (GSE) vehicles and equipment operated by Ground Handling Companies on the air side of Sultan Thaha Jambi Airport. As well as evaluating the role of the Apron Movement Control Unit in supervision and maintenance. The background of this study found various technical problems, such as broken brakes, dead sign lights, oil leaks, bald tires, and fire extinguishers that are not suitable for use. Maintenance procedures by the Ground Handling Company are still reactive and not consistently carried out preventively. The research method used is a descriptive qualitative method with data collection techniques through field observations, interviews with AMC and Ground Handling personnel, and documentation. The results showed that most of the GSE vehicles and equipment in operation have not fully met the eligibility standards according to KP 635 Year 2015. Supervision by the AMC Unit has not been optimal, characterized by many undetected violations. This study concludes that strengthening supervision by the AMC unit, implementing a digital system for reporting and inspection, and improving operator discipline through retraining and administrative witnesses are needed. This strategy ensures that the safety of airside flight operations is maintained and in accordance with applicable standards